2013
DOI: 10.1177/0269215513504943
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic therapy improves pain, disability, quality of life, body composition and fitness in sedentary adults with chronic low back pain. A controlled clinical trial

Abstract: A two-month intensive aquatic therapy programme of high-frequency (five times/week) decreases levels of back pain and disability, increases quality of life, and improves body composition and health-related fitness in sedentary adults with chronic low back pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
86
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(98 citation statements)
references
References 36 publications
3
86
0
9
Order By: Relevance
“…No further studies were found by checking reference lists. Twenty quantitative publications and two qualitative publications were excluded at this stage. Excluded publications are listed with reasons for exclusion (SI4).…”
Section: Resultsmentioning
confidence: 99%
“…No further studies were found by checking reference lists. Twenty quantitative publications and two qualitative publications were excluded at this stage. Excluded publications are listed with reasons for exclusion (SI4).…”
Section: Resultsmentioning
confidence: 99%
“…The association between body composition, low back pain, and disability has been examined that low back pain was shown to be associated with significant improvement of body composition such as weight, body mass index, body fat percentage, and skeletal muscle mass (Baena-Beato et al, 2014). These results imply that positive changes to manage one’s body composition components may reduce the risk of back pain.…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity is an important lifestyle behavior that contributes to body weight regulation, and therefore may be important for both prevention and treatment of overweight and obesity, as previous studies have demonstrated (Baena-Beato et al, 2014;E. F. Nagle et al, 2007).…”
Section: Discussionmentioning
confidence: 99%